Analysis of The Implementation of KITE IKM Policy in Indonesia - Lu'lu' Nurul Jannati; Bernardus Yuliarto Nugroho (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the implementation of the Ease of Import Facilities for Export-Oriented Small and Medium Industries (Kemudahan Impor Tujuan Ekspor untuk Industri Kecil dan Menengah/KITE IKM) policy and explore the factors affecting its implementation based on Grindle’s policy implementation model. Research Methodology: This study employs a qualitative approach using Grindle’s policy implementation model for the analysis. Data were collected through interviews and document and literature reviews. Results: Policy implementation is hindered by various constraints, including the absence of quantitative targets, limitations in the performance measurement system for facility beneficiaries, and insufficient inter-agency coordination in supporting the empowerment of export-oriented Small and Medium-sized Enterprises (SMEs). In terms of implementation factors, weaknesses such as a limited understanding of the target group, suboptimal outreach, and uneven implementation strategies across the Digital Green Communication Engagement (DGCE’s) operational regions persist. Conclusions: Optimizing the KITE IKM program requires not only improvements in policy implementation but also strengthening the export SME ecosystem through more integrated inter-agency collaboration to support capacity building and SMEs exports. Limitations: This study is limited to the implementation of the KITE IKM policy during 2017-2025 employing Grindle’s policy implementation framework. Contributions: This study contributes to the literature on policy implementation and provides practical insights for policymakers, particularly the DGCE, to improve the implementation of the KITE IKM program and strengthen MSME empowerment and export participation.